Connection coefficients of Shannon wavelets - Cattani, C. (Mathematical Modelling and Analysis, 2006)
In this paper the differential properties of Shannon wavelets are investigated. The connection coefficients of Shannon wavelets are explicitly computed with a finite formula up to any order. First Published Online: 14 Oct 2010